2016
DOI: 10.1037/xge0000170
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of adaptive and fixed schedules of practice.

Abstract: Understanding and optimizing spacing of learning events is a central topic in basic research in learning and memory and has widespread and substantial implications for learning and instruction in real-world settings. Spacing memory retrievals across time improves memory relative to massed practice – the well-known spacing effect. Most spacing research has utilized fixed (predetermined) spacing schedules. Some findings indicate advantages of expanding spacing intervals over equal spacing (e.g., Landauer & Bjork… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 48 publications
(114 reference statements)
0
34
0
Order By: Relevance
“…Such predictions, if valid, could be used to prescribe personalized review (Mettler et al, 2016;Pavlik & Anderson, 2008). Such predictions, if valid, could be used to prescribe personalized review (Mettler et al, 2016;Pavlik & Anderson, 2008).…”
Section: Make Precise Predictions and Valid Prescriptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such predictions, if valid, could be used to prescribe personalized review (Mettler et al, 2016;Pavlik & Anderson, 2008). Such predictions, if valid, could be used to prescribe personalized review (Mettler et al, 2016;Pavlik & Anderson, 2008).…”
Section: Make Precise Predictions and Valid Prescriptionsmentioning
confidence: 99%
“…To be maximally useful, a computational model of the spacing effect should make individual-level out-of-sample temporal predictions. Such predictions, if valid, could be used to prescribe personalized review (Mettler et al, 2016;Pavlik & Anderson, 2008). We have begun to explore this issue in PPE and have found that the model can, in fact, make accurate individualized predictions for a range of skill-based and declarative tasks (Jastrzembski et al, 2017).…”
Section: Make Precise Predictions and Valid Prescriptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spacing effect has been studied extensively over time, with large effect sizes giving evidence of its robust effectiveness in increasing long term retention (Dunlosky, Rawson, Marsh, Nathan, & Willingham, 2013;Kapler, Weston, & Wiseheart, 2015;Mettler, Massey, & Kellman, 2016;Rohrer, Dedrick, & Stershic, 2015). In these studies, it was more effective to space out practice on a topic than to mass practice all at once.…”
Section: Spaced and Interleaved Learningmentioning
confidence: 99%
“…The literature consistently shows that spacing learning is a simple, robustly effective technique that can increase long term retention (Dunlosky et al, 2013;Kapler et al, 2015;Mettler et al, 2016). intervention group students were required to complete three different practice slips correctly on three different days, which built spaced learning into the intervention.…”
Section: Mathematics Classroom Interventionsmentioning
confidence: 99%